2021
DOI: 10.1111/evj.13412
|View full text |Cite
|
Sign up to set email alerts
|

Practical protocols for timed artificial insemination of jennies using cooled or frozen donkey semen

Abstract: Background: With the expansion of the donkey industry, timed artificial insemination (TAI) is becoming increasingly important in the reproductive management of jennies, however, TAI has not been widely investigated in donkeys.Objectives: To develop efficient TAI protocols for cooled or frozen semen in jennies, based around ovulation induction with a GnRH analogue.Study design: Experimental exploratory study. Methods and Results:In experiment 1, the effects of different GnRH analogue (deslorelin) doses, follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…To date, there is no gold standard protocol for cooling donkey semen, and clinical experience suggests that donkey semen has poor fertility and cooling ability when extended in commercially available equine SM-or milk-protein-based extenders (2). Even though some authors propose that this poor cooling ability may be circumvented by centrifuging jack semen to remove seminal plasma or adding 2% egg yolk to SM extenders, research is limited in this aspect and published results vary according to protocols (5,7,(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is no gold standard protocol for cooling donkey semen, and clinical experience suggests that donkey semen has poor fertility and cooling ability when extended in commercially available equine SM-or milk-protein-based extenders (2). Even though some authors propose that this poor cooling ability may be circumvented by centrifuging jack semen to remove seminal plasma or adding 2% egg yolk to SM extenders, research is limited in this aspect and published results vary according to protocols (5,7,(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have reported fertility rates of cooled donkey semen ranging from 21 to 76% using extenders with different bases, the average period of storage in the majority of studies has been short (e.g., 2–8 h) ( 24 26 ) or mares were inseminated several times in the same estrous cycle ( 13 , 63 ). Therefore, in our previous study with cooled donkey semen ( 14 ), the authors deliberately mimicked conditions in equine practice where semen is often shipped over long distances for 24–48 h ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided improvements to OPU in equines through gonadotropin treatment for 36 h before aspirating, and the recovery rate increased to nearly 70% (Morris, 2018). Previous report from our laboratory showed that GnRHa was efficient in inducing ovulation in donkeys, with more than 90% of donkeys ovulating within 48 h (Yang et al, 2021). Our results showed that the recovery rate of donkey preovulatory follicles (≥35 mm) after 24 h of GnRHa treatment was 72.2%, which is similar to equines (Carnevale et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…In this latter context, ovulation induction with a GnRH analogue was also recently shown to improve pregnancy rates in a donkey AI programme, despite reducing the frequency with which follicle development was monitored. In jennies, administering a GnRH analogue when the pre‐ovulatory follicle reached 31–35 mm appeared to be the optimal basis for fixed‐time AI using either chilled semen (AI 8 hours after GnRH analogue administration) or low doses of frozen‐thawed semen (AI 34 and 42 hours after GnRH) 3 ; achieving pregnancy rates of ~30% per cycle with as few as 100 million motile frozen‐thawed spermatozoa was particularly noteworthy given that previous studies have struggled to achieve commercially acceptable pregnancy rates using frozen‐thawed donkey semen.…”
Section: Ensuring Spermatozoa and Oocyte Meet At The Right Time And Right Placementioning
confidence: 99%